Nematode resistance screening in Musa Spp. using macropropagated plantlets - Olajide, E.; Cortada, L.; Saikai, K.; Amah, D.; Coyne, D.; Bert, W.; Swennen, R.; Kolombia, Y.A. (2025)
This study evaluated macropropagated plantlets for nematode resistance screening in Musa spp. We aimed to determine the optimal timing for assessing resistance to Radopholus similis and Meloidogyne arenaria in the plantain cultivar ‘Agbagba’ at 30-, 60-, and 90-days post-inoculation (DPI). Additionally, we tested different substrates for early-stage screening at 7 DPI. Results indicated that 60 DPI is optimal for resistance screening against R. similis due to significant root damage, while M. arenaria reproduction peaked at 90 DPI without extensive root deterioration. The sand-absorbent polymer (SAP) substrate was most effective for early nematode penetration. Using these findings, we assessed five Musa genotypes at 60 DPI; ‘SH 3142’ and ‘Pisang Jari Buaya’ showed resistance to R. similis, ‘Agbagba’ was susceptible, ‘Yangambi KM5’ was unexpectedly susceptible, and ‘Pisang Lilin’ showed intermediate resistance. This study highlights that macropropagated plantlets can be used as an effective method for rapid preliminary resistance screening in Musa spp.